2000
DOI: 10.3109/03005364000000131
|View full text |Cite
|
Sign up to set email alerts
|

A Test for the Diagnosis of Dead Regions in the Cochlea

Abstract: Hearing impairment may sometimes be associated with complete loss of inner hair cells (IHCs) over a certain region of the basilar membrane. We call this a 'dead region'. Amplification (using a hearing aid) over a frequency range corresponding to a dead region may not be beneficial and may even impair speech intelligibility. However, diagnosis of dead regions is not easily done from the audiogram. This paper reports the design and evaluation of a method for detecting and delimiting dead regions. A noise, called… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
395
3
10

Year Published

2004
2004
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 395 publications
(414 citation statements)
references
References 26 publications
6
395
3
10
Order By: Relevance
“…This technique 10 showed very strong agreement with the above criteria indicative of possible ZMC 25 and showed that white noise has an effect similar to the threshold equalizing noise (TEN) 27 , which is internationally recognized as a simple and efficient method for identifying possible ZMC. Therefore, the masking test by white noise is considered as a reliable alternative for identifying the possible presence of ZMC.…”
Section: Classification Of Subjects In the Groups: Identification Of mentioning
confidence: 68%
See 1 more Smart Citation
“…This technique 10 showed very strong agreement with the above criteria indicative of possible ZMC 25 and showed that white noise has an effect similar to the threshold equalizing noise (TEN) 27 , which is internationally recognized as a simple and efficient method for identifying possible ZMC. Therefore, the masking test by white noise is considered as a reliable alternative for identifying the possible presence of ZMC.…”
Section: Classification Of Subjects In the Groups: Identification Of mentioning
confidence: 68%
“…When the masked thresholds obtained were at least 10 dB above the absolute threshold and the masking level used, the result was considered indicative of the presence of ZMC 27 .…”
Section: Classification Of Subjects In the Groups: Identification Of mentioning
confidence: 99%
“…Dead regions. Following the pitch scaling experiment dead region diagnostics were undertaken using a the Threshold Equalizing Noise (TEN) test (Moore et al, 2000). This test was the last in the sequence of test to exclude the bias that could occur when choosing upper anchors for the pitch scaling experiment after knowledge of possible dead regions.…”
Section: Tests and Proceduresmentioning
confidence: 99%
“…For this purpose, we utilized the Threshold Equalizing Noise (TEN) test of Moore et al (2000). The main feature of this diagnostic screening tool is to present a broad-band noise (at different levels), that is designed in such a way that equal noise power (calibrated in SPL) is contained in all cochlear auditory output filters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation